Capacity and market potential for local production and distribution of electric two-wheelers in Southeast Asia, focused on Thailand, Indonesia and Vietnam - Hyung Ju Kim; Shritu Shrestha; Kanya Pranawengkapti (Sustainable Earth Reviews)
Abstract Although international efforts toward vehicle electrification in Southeast Asia have primarily focused on four-wheeled vehicles, greater emphasis must be directed toward two-wheeled vehicles (2 W). Southeast Asia has the world’s highest rate of 2 W penetration, particularly in Thailand, Vietnam, and Indonesia. These vehicles are popular in this region mainly due to the limited public transportation, their agility on narrow roads, and their ability to maneuver through heavy traffic. Additionally, 2Ws provide a flexible and affordable transportation option, significantly enhancing accessibility and last-mile connectivity to existing public transit networks. However, the vast majority of 2Ws in the region still rely on internal combustion engine (ICE), contributing significantly to urban air pollution and greenhouse gas emissions. Considering the significant role of 2Ws in transporting people and goods throughout Southeast Asia, electrifying this sector offers a substantial potential to mitigate climate impact. This paper advocates for collaborative initiatives across digital platforms, financial mechanisms, and supportive government policies to accelerate the adoption of electric 2Ws (E2Ws) by promoting local production, fostering innovative business models, and establishing conducive regulatory frameworks. A robust E2Ws ecosystem, local E2Ws in the region will require increased cooperation among local E2W and charging equipment manufacturers within the global supply chain, ensuring the development and distribution of environmentally sustainable, technologically advanced, and competitively priced products. Furthermore, E2Ws producers must develop and implement various innovative business models, particularly around battery reuse and recycling, developed in partnership with market stakeholders, including digital platform companies with high growth potential. The financial sector can play a crucial role by creating advanced financing solutions to ease consumer access to E2Ws. Lastly, the governments must support this transition through both financial and non-financial policies, including technical standards, offer preferential policies for E2Ws and charging equipment, and facilitating rapid development. Clinical trial number: Not applicable.